THE RELATIONSHIP OF MODERN DRESSING CARE METHODS WITH PATIENT SATISFACTION IN CARING DIABETES MELITUS AT PMI HOSPITAL BOGOR: HUBUNGAN METODE PERAWATAN LUKA MODERN DRESSING DENGAN TINGKAT KEPUASAN PASIEN DALAM PROSES PERAWATAN LUKA DIABETES MELITUS DI RS PMI KOTA BOGOR - Tri Tri Diani Agustuti; Yufi Yufi Aliyupiudin (Jurnal Ilmiah Wijaya, 2019)
The level satisfaction of patients where feeling happy or disappointed in patients with diabetes mellitus after getting wound care at the wocare center clinic, because there are several reasons, for example to reduce the risk of infection and amputation, improve function and quality of life. This study aims to identify the level of satisfaction of DM wound patients on wound care for modern dressing at the bogor city wocare center clinic.The purpose of this study was to determine the relationship of Modern Dressing Wound Care Methods to the Level of Patient Satisfaction in the PMI Hospital Bogor 2018. This research type is an analytical survey with a cross sectional approach. The method of sampling in this study uses Slovin techniques with a sample are 80 respondents. Patient satisfaction status data were obtained are giving by questionnaires and observing wound care.The results of univariate analysis based on the frequency distribution of treatment methods mostly did not use Modern Dressing wound care as much as 41 patients (52%) and the frequency distribution of samples based on the level of patient satisfaction in the treatment process of Bogor 2018 mostly as many as 41 patients (52%).The results of bivariate analysis using the Creamers test, the proportion of respondents with more patient satisfaction results than clients who were dissatisfied with the wound care process (51,2% vs 48,8% with ρ = 0.001; ρ <0.05), so Ho was rejected with Ha accepted which means that there is a relationship between modern wound care and the level of patient satisfaction. Based on the conclusions of the research results, there are suggestions for medical staff in the clinic to maintain and improve services so that patients are more satisfied in the service process.